101 design methods : a structured approach for driving innovation in your organization - Kumar, Vijay (Wiley, 2013)
A guide for successful innovation planning. It is suitable for strategists, managers, designers, and researchers who undertake the challenge of innovation, despite a lack of established procedures and a high risk of failure